2019
DOI: 10.1109/jbhi.2018.2827100
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Quantification of Impact of Psychological Factors on Rehabilitation of Stroke Patients

Abstract: The brain damage could lead to the loss of the central nervous system, so a stroke patient may lose the function of dominating his/her body. The rehabilitation aims to maximize the potential to restore a patient who has an impairment. Traditional rehabilitation is to train a patient's muscles and joints under the guide of doctors to improve the strength of muscles and restore the motor function of joints. However, stroke patients are usually depressed, lonely and irritable, and they might easily generate negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…Beside of these, we also found some brain regions with predictive weights related to mental and psychological aspects, such as the contralesional putamen (Klingbeil et al, 2022), the contralesional occipital lobe (Park et al, 2011), the ipsilesional frontal lobe (Stangeland et al, 2018), the ipsilesional orbital gyrus (Pan et al, 2022), etc. Some studies have also reported that psychosocial factors and non-motor brain regions have an impact on stroke rehabilitation Qian et al, 2019). As can be seen, the ROIs we extracted involved motor and mental brain regions, and could be used as features to more comprehensively predict the classification of motor recovery after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Beside of these, we also found some brain regions with predictive weights related to mental and psychological aspects, such as the contralesional putamen (Klingbeil et al, 2022), the contralesional occipital lobe (Park et al, 2011), the ipsilesional frontal lobe (Stangeland et al, 2018), the ipsilesional orbital gyrus (Pan et al, 2022), etc. Some studies have also reported that psychosocial factors and non-motor brain regions have an impact on stroke rehabilitation Qian et al, 2019). As can be seen, the ROIs we extracted involved motor and mental brain regions, and could be used as features to more comprehensively predict the classification of motor recovery after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…(5,6) Namun, metode intervensi ini memerlukan pendekatan langsung dengan terapis dalam waktu yang lama dan memerlukan pembiayaan pengobatan yang mahal. (7) Disisi lain, suatu terapi biasanya fokus pada aspek-aspek berikut: bagian tubuh yang dilatih (misalnya kaki, tangan atau mulut), alat atau mesin yang digunakan untuk melatih (misalnya, treadmill, cermin), aktivitas yang dilakukan (misalnya, berjalan, menggenggam dan perawatan diri), dan waktu yang tepat untuk memulai terapi post stroke (misalnya, segera dimulai saat memasuki fase akut). (8) Intervensi pasien post stroke bisa saja dengan membatasi penggunaan anggota tubuh yang normal dan berfokus pada yang mengalami disabilitas, dan terapis dapat mendorong pasien mandiri dalam rehabilitasi namun memiliki dampak yang signifikan.…”
Section: Abstrakunclassified
“…However, motivation is significantly neglected in both clinical practice and research studies on motor rehabilitation ( Robertson, 2013 ; Verrienti et al, 2023 ). A common issue is that patients often experience frustration and lack enthusiasm to attend training sessions due to post-stroke depression or the prolonged training period with minimal progress ( Qian et al, 2019 ). Low motivation leads to decreased efficiency and unsatisfactory motor improvement.…”
Section: Introductionmentioning
confidence: 99%